Evaluating the Impact of School Counseling Programs on Student Well-being and Academic Performance in the Educational Environment - Simbolon, Roventus; Purba, Widitra (Insan Akademika Publications, 2022)
This research evaluation investigates the influence of guidance and counseling programs in school settings, focusing on their effects on student well-being, academic performance, and the overall school environment. A mixed-methods approach was employed, encompassing quantitative data analysis and qualitative insights. The quantitative analysis yielded significant results, demonstrating a marked improvement in academic performance among students who actively engaged with counseling programs. Furthermore, these students exhibited a noteworthy rise in attendance rates, attending school 10% more regularly than their peers who did not participate in counseling. The qualitative analysis offered deeper insights, revealing personal growth as a recurrent theme among students. Participants cited the development of problem-solving skills, increased self-esteem, and enhanced self-confidence as critical outcomes. Additionally, improved interpersonal relationships and a harmonious school environment were reported, indicating a broader impact on the school community. The commitment to inclusivity and equity underscored the need to ensure that all students, regardless of their background or circumstances, have equal access to counseling services. This inclusivity promotes a more equitable educational environment. These findings carry implications for the field of guidance and counseling in schools. They underscore the pivotal role of counselors in fostering student success, both academically and emotionally. The results call for a holistic approach to student development, emphasizing the importance of early intervention, inclusivity, and creating positive school cultures. This research offers a pathway to strengthening guidance and counseling programs, ultimately enhancing the educational experience for students. It serves as a catalyst for the field, driving the evolution of guidance and counseling to create a nurturing and inclusive educational environment where every student can thrive academically and emotionally.